AutoCAD 2002 Instructor - Leach James A. (McGraw -Hill, 2001)
Developed from teaching techniques used in an authorized AutoCAD Training Center and in instruction for engineering colleges, AutoCAD 2000 Instructor covers all features and capabilities of AutoCAD. The text is command-oriented so chapters are centered around groups of related commands. This feature makes the text very effective as a reference text. The chapters are structured in a practical/pedagogical sequence beginning with instruction in general procedures for using the computer interface, setting up and creating drawings, and then progressing to advanced features such as dimensioning, special drawing applications and AutoCAD features, three-dimensional modeling and rendering, and software customization.